2006
DOI: 10.1007/s00125-006-0353-x
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the relationship between the ENPP1 K121Q polymorphism and type 2 diabetes, insulin resistance and obesity in 7,333 Danish white subjects

Abstract: Aims/hypothesis Plasma cell membrane glycoprotein 1 (PC-1) inhibits insulin signalling by direct interaction with the insulin receptor α subunit. This inhibition is enhanced by the minor Q allele of the K121Q polymorphism (rs1044498) in the gene (ENPP1) encoding PC-1. This polymorphism has been studied in relation to insulin resistance, type 2 diabetes and obesity in several populations with conflicting results. We assessed the impact of the ENPP1 K121Q polymorphism on type 2 diabetes, obesity and quantitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
70
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(78 citation statements)
references
References 45 publications
6
70
1
1
Order By: Relevance
“…To identify the populations to be included in this study, we initially selected all of the relevant case/control studies reported in previous meta-analyses of ENPP1 that assessed association results with type 2 diabetes (13,14,16,17), the largest consisting of 7,318 case and 13,726 control subjects (17). We complemented this approach with a systematic review of the PubMed database for articles that included "ENPP1" as a keyword, last accessed in August 2007.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To identify the populations to be included in this study, we initially selected all of the relevant case/control studies reported in previous meta-analyses of ENPP1 that assessed association results with type 2 diabetes (13,14,16,17), the largest consisting of 7,318 case and 13,726 control subjects (17). We complemented this approach with a systematic review of the PubMed database for articles that included "ENPP1" as a keyword, last accessed in August 2007.…”
Section: Methodsmentioning
confidence: 99%
“…A French and Austrian study, consisting of 1,255 case and 1,314 control subjects, examined several polymorphisms in ENPP1 and found evidence that a three-marker haplotype (comprised by K121Q as well as (18). Partial meta-analyses reported by the first two publications (16,17) yielded a nominal association of the Q allele with type 2 diabetes, but they continued to show significant heterogeneity and did not include results from each other or from our own extensive dataset. Similar limitations are present in a recent review (19).…”
mentioning
confidence: 99%
“…One ENPP1 haplotype is associated with childhood and morbid obesity, T2DM, as well as circulating levels of ENPP1. [144][145][146] Expression of a long ENPP1 mRNA isoform, which includes one of the SNPs defining the risk haplotype, is specific for pancreatic islet beta cells, adipocytes and liver. 144 In addition, one ENPP1 SNP may impair insulin binding to the insulin receptor.…”
Section: Pathways Controlling Lipid Storage In Adipocytesmentioning
confidence: 99%
“…26 However, contrary results were also reported between K121Q and T2D in the Asian and Caucasian population. [27][28][29][30][31][32][33] In addition, recent genome-wide association studies have revealed a series of predisposing SNPs of T2D, which are mostly related to insulin secretion rather than to insulin resistance, 34 in large-scale samples and gene pool, but no evidence of association, except one, 21 between ENPP1 and T2D has been reported. [3][4][5] In our study, we examined two representative SNPs of ENPP1, rs1044498 (K121Q) and rs7754561, and investigated the possible association between them and T2D and obesity in a Chinese case-control population, which had been the largest sample investigated in China so far.…”
Section: Introductionmentioning
confidence: 99%